NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU “MUTIARA BANGSA TOMBAK NEGARA” KARANGAN HENDRA PERMANA DAN RELEVANSINYA DENGAN ANAK USIA SEKOLAH DASAR: (Studi Deskriptif pada Buku Mutiara Bangsa Tombak Negara ‘’Karangan Hendra Permana’’) - Aprilyani, Alisa; Nuriyanti, Risma (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2021)
This research is qualitative research. This type of research is library research. Data collection is done with library studies, data cards and documentation. Based on the results of research and the results of this simple percentage calculation shows the dominant character education values highlighted in the book among others. Chapter 1 (17%), Chapter 2 (28%), Chapter 3 (34%), Chapter 4 (12%), Chapter 5 (23%), Chapter 6 (45%), chapter 7 (23%) in , Overall researchers concluded that the most dominant character education value highlighted from the 7 most superior chapters is Chapter 6 which is the value of character curiosity (45%). While the relevance to primary school children is adjusted to the Core Competency (1) religious and (2) Social in accordance with Regulation of the Minister of Education and Culture No. 37 of 2018 which includes religious value characters, honesty, tolerance, discipline, hard work, creative, self-independence, curiosity, national spirit, appreciating achievement, peace of mind, love of reading, and social care.